Impact of Insurance Scheme on Adults’ Dental Check-Ups in a Developing Oral Health Care System - Bayat, Fariborz; Vehkalahti, Miira M; Zafarmand, A. Hamid; Tala, Heikki (European Journal of Dentistry, 2008)
Objectives: To find out the relationship between dental insurance and demand for dental care, the present study evaluated impact of insurance scheme on adults’ dental check-ups in a developing oral health care system.Methods: The target population included adults in the city of Tehran where the only telecommunication company provides 90% of the 1.9 million households with a fixed telephone. Of the 1531 subjects who answered the phone call, 224 were outside the target age (under 18), 67 said that they never had visited a dentist, and 221 refused to respond, leaving 1019 subjects in the final sample. Each interview lasted 15 minutes and was carried out using a structured questionnaire with fixed and open-ended questions.Results: 71% of the subjects reported having dental insurance and 16% having visited a dentist for a check-up; 55%, more women than men, reported having had a dental visit within the past 12 months.Conclusions: The present results revealed the positive relationship between insurance and demand for dental care. Those having dental insurance were more likely to go to check-ups despite their generally low rate found in this country with a developing oral health care system. In such countries, health insurance schemes should therefore include obligatory regular dental check-ups to emphasize prevention-oriented dental care. (Eur J Dent 2008;2:3-10)
Keywords: Adults; Dental check-ups; Dental visit; Demand; Dental insurance